Assisting Tourism Supply Chain Performance in Thailand through Big Data Analytics: Moderating Role of IT Capability - Chayanan Kerdpitak; Chattrarat Hotrawaisaya; Martusorn Khaengkhan (International Journal of Supply Chain Management, 2019)
Oxygen of Thailand’s economy is its tourism industry which has also geared up all related sectors too. Country is making a lot of efforts to achieve sustainable tourism supply chain performance through Big Data Analytics (BDA) as without BDA, it was never possible to move towards sustainability for such a big industry. However, IT capability seems a missing piece in some cases which can decrease the effectiveness of BDA dimensions. Author has aimed to analyze the impact of BDA planning, investment, coordination and control on sustainable tourism development in moderating role of IT capability. Sample was consisted of those hotels and hospitality industry units which already have BDA system in operational phase and their employees were surveyed through questionnaire and responses were then analyzed on SPSS and AMOS for hypotheses testing. Results have enlightened that BDA dimensions have significant positive impact on sustainable tourism supply chain performance while IT capability was also found as positive and significant moderator too. None of the previous studies have taken IT capability as moderator but this originality in this study has long lasting implications for tourism and manufacturing industry to induce IT capability in their organizations to achieve sustainability.